BDNF Modulates, But Does Not Mediate, Activity-Dependent Branching and Remodeling of Optic Axon Arbors In Vivo - Cohen-Cory, Susana (J Neurosci, 1999)
The proper development of axon terminal arbors and their recognition of target neurons depend, in part, on neuronal activity. Neurotrophins are attractive candidate signals to participate in activity-dependent development and refinement of neuronal connectivity. In the visual system, brain-derived neurotrophic factor (BDNF) has been shown to modulate the elaboration and refinement of axonal arbors and to participate in the establishment of topographically ordered visual maps. By examining in vivo with time-lapse microscopy the effects of activity blockade and BDNF on optic axon arborization, I show that the dynamic mechanisms by which neurotrophins and neuronal activity regulate axon arborization differ. Acute retinal activity blockade by intraocular injection of tetrodotoxin (TTX) rapidly and significantly increased branch addition and elimination, thus interfering with axon branch stabilization. The effects of activity blockade on branch dynamics resulted in increased arbor complexity in the long term and were prevented by altering endogenous BDNF levels at the target. BDNF promoted axon arborization by increasing branch addition and lengthening, without affecting branch elimination. Activity blockade, however, did not prevent the growth-promoting effects of BDNF, indicating that BDNF can affect axon arborization even in the absence of activity. Together this evidence indicates that BDNF acts as a modulator, but not as a direct mediator, of activity during the morphological development of neurons. Consequently, neuronal activity and BDNF use distinct but interactive mechanisms to control the development of neuronal connectivity; BDNF modulates axon arborization by promoting growth, neuronal activity participates in axon branch stabilization, and together these two signals converge to shape axon form.